PHYLLODES TUMORS OF THE BREAST: A RETROSPECTIVE EVALUATION OF CASES FROM THE HOSPITAL DO SERVIDOR PÚBLICO ESTADUAL DE SÃO PAULO - Matos, Ana Beatriz Tavares de Moura Brasil; Araujo Neto, Joaquim Teodoro de; Antonini, Marcelo; Ferraro, Odair; Mancinelli, Bruno de Carvalho; Pereira, Ana Maria Gomes; Lopes, Reginaldo Guedes Coelho (Mastology, 2017)
Objective: To evaluate the clinical and pathological characteristics of phyllodes tumors, and to identify possible associated risk factors for relapses among patients from the Breast Surgery Department of the Hospital do Servidor Público Estadual of São Paulo (HSPE-SP). Methods: Retrospective, descriptive study of data from 52 patients, between 1976 and 2013. The following data were collected: age, tumor size, histological type, surgical margins, type of surgery performed, relapses and amount of time before relapse. Results: The mean age of the patients was 45.7 years old, the mean size of the tumor was 7.8 cm. A mastectomy was performed on 12 patients, and the others underwent a wide excision. Benign phyllodes tumors were found in 30 patients, and the others were found as follows: 11 with borderline tumors and 11 with malign phyllodes tumors. There was no statistical relevance with regard to the relapses and the characteristics evaluated. Conclusion: The sample studied has similar clinical and pathological characteristics as described in the scientific literature, with the mean age at diagnosis being 45 years old, the mean tumor size, 7.8 cm. The majority found were benign phyllodes tumors and 33% were from relapses. There was no statistical significance between the evaluated variables and the risk for relapse.